ANALIZĂ DE CONȚINUT A ARIILOR STRATEGICE DE SECURITATE CIBERNETICĂ – STATELE UNITE ALE AMERICII, MAREA BRITANIE, SPANIA ȘI ROMÂNIA (CONTENT ANALYSIS OF STRATEGIC CYBER SECURITY FOCUS AREAS – UNITED STATES OF AMERICA, UNITED KINGDOM, SPAIN AND ROMANIA) - Cristian CONDRUȚ (Intelligence și Cultura de Securitate)
Nowadays cybersecurity is a topic that is more extensively addressed at a strategic level, both form a technical as well as form a non-technical perspective. In this context, the most important international organizations address cybersecurity by organizing international discussions aimed at keeping an open, free and secure cyberspace. These endeavours are usually taking the form a policy paper, a recommendation guide or a common initiative signed by multiple states. This kind of practice requires a correspondent in national strategic policy papers, the most important one being the national cybersecurity strategy. Taking into consideration that cybersecurity is not only a technical matter, multiple strategic areas are needed to be addressed. Thus, in this paper we aim to identify the most important cybersecurity strategic areas at a national level and their corelations. To achieve this research objective, we apply a content analysis and a frequency analysis methodology, using MAXQDA 20222 software. Our findings show that cybersecurity governance strategic area and preparedness and resilience strategic area are the most important ones at a national level, having multiple corelations with other strategic areas retrieved from the Guide to Developing a National Cybersecurity Strategy published by International Telecommunications Union in 2021.